2018
DOI: 10.14283/jfa.2018.16
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between 6-Point Dixon Mri and MR Spectroscopy to Quantify Muscle Fat in the Thigh of Subjects With Sarcopenia

Abstract: Background: Changes in muscle fat composition as for example observed in sarcopenia, affect physical performance and muscular function, like strength and power. Objectives: The purpose of this study was to compare 6-point Dixon magnetic resonance imaging and multi-echo magnetic resonance spectroscopy sequences to quantify muscle fat. Setting, participants and measurements: Two groups were recruited (G1: 23 healthy young men (28 ± 4 years), G2: 56 men with sarcopenia (80 ± 5 years)). Proton density fat fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…[54] For these advanced MRI applications, Dixon-based MRI sequences resulted to be more reliable and easier to be handled than spectroscopy Dixon [53]. Both singlevoxel and multi-voxel spectroscopy, the latter with the goal to overcome the irregular pattern of muscle fatty or scar infiltration, have been reported for sarcopenia assessment, but [55][56][57] with difficult implementation in clinical practice. Muscular contractility and elasticity have been studied using MRI [58] with sequences adopting strain rate tensor measures detecting the principal directions and magnitude of the instantaneous deformation providing information on the alignment of muscular fibers orientation and deformation in the plane perpendicular to the muscle long axis.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…[54] For these advanced MRI applications, Dixon-based MRI sequences resulted to be more reliable and easier to be handled than spectroscopy Dixon [53]. Both singlevoxel and multi-voxel spectroscopy, the latter with the goal to overcome the irregular pattern of muscle fatty or scar infiltration, have been reported for sarcopenia assessment, but [55][56][57] with difficult implementation in clinical practice. Muscular contractility and elasticity have been studied using MRI [58] with sequences adopting strain rate tensor measures detecting the principal directions and magnitude of the instantaneous deformation providing information on the alignment of muscular fibers orientation and deformation in the plane perpendicular to the muscle long axis.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…This finding might be applied to identify diseases at an early stagediseases, when they theoretically could still be reversible. Recently, comparing Dixon and 1 H-MRS similar levels of accuracy and repeatability in assessing the fat fraction have been demonstrated (24,49). It has to be highlighted that 1 H-MRS has the capability of distinguishing between intramyocellular and extramyocellular lipid components whereas Dixon maps of the fat fraction distribution can be especially useful for "patchy" physio-pathological processes such as fibro-fatty replacement areas.…”
Section: A B C D a Bmentioning
confidence: 97%
“…In in-vivo and phantom-based studies, Dixon showed high accuracy for the assessment of fatty replacement of muscles in dystrophic patients (49,50). Moreover, it has been successfully applied for evaluating muscle atrophy, adipose infiltration and interstitial fibrosis of denervated skeletal muscle due to traumatic injuries of the brachial plexus (46,48).…”
Section: Chemical-shift Based Imagingmentioning
confidence: 99%
“…The additionally rather long acquisition times and the need for a prospective acquisition, further prevent large scale use of this technique beyond scientific studies. While MR spectroscopy has existed even before clinical MR imaging and is still often considered as the gold standard of volumetric fat quantification (68,69), current clinical investigations predominantly focus on chemical shift imaging (70). Nonetheless, MR spectroscopy is still used frequently in research settings, also due to recent discoveries in the field of in-vivo muscle function assessment with 31-P-spectroscopy (71,72).…”
Section: Diffusion-weighted Imaging and Mr Spectroscopymentioning
confidence: 99%